Analysis of the Mean Gray Scale and the Mandibular Thickness (Micro-CT) To Mandibular bone Density in Synthetic SCAFFOLD-hADMSC - Latief Mooduto1 , Arief Rahman2 , Fedik A Rantam3 , Jenny Sunariani4 , Hendy Jaya Kurniawan5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction. The concept of biofactor transplantation in porous and degradable materials as scaffolds is aplace for regenerating new cell and bone tissue growth in the application of tissue engineering. Human AdiposeDerived Mesenchymal Stem Cells (hADMSC) is a multipotent cell which has osteogenic, chondrogenic, andadipogenic potential. It also has somany similar characteristics with Bone Marrow stem cells (BMSCs) buthADMSC has higher proliferation rate compared to BMSCs.Inspite of this, another ability of biofactors isgene engineering. Aim. This study aimed to analyze mandibular bone density from the synthesis of scaffoldhADMSC with the mean gray scale and the mandibular bone thickness (Micro-CT).Material and Methods.This research involved several processes, namely synthetic scaffold manufacturing process, differentiationand characterization of hADMSC, and Micro-CT. Results. The results of the marked expression of thecharacterization of hADMSCand analysis of the mean gray scale and mandibular thickness (Micro-CT) tomandibular bone density in synthetic scaffold-hADMSC showed to be significant. Conclusions. Syntheticscaffold-hADMSC can increase mandibular bone density after Micro-CT analysis.